Formative Evaluation of an Online Responsive Feeding Training Program for Early Childhood Education Professionals (P11-068-19). (13th June 2019) - Savage, Jennifer; Hess, Lindsey; Dattilo, Anne; Sigman-Grant, Madeleine; Ward, Dianne Stanton; Shuell, Julie
Abstract: Objectives: With most US children enrolled in center-based childcare, there is a critical need for responsive feeding (RF) training and resources that target early childcare. This study explores the feasibility and user acceptability of an interactive online RF training program tailored for Early Childhood Education (ECE) providers of infants and young toddlers. Methods: The RF program was developed by the investigators, with aid from a digital educational agency, and input from additional nutrition and early childhood experts. ECE providers (n = 27) completed an enrollment survey, knowledge pre-test, and interview about RF training and beliefs prior to gaining access to four RF modules (Overview; Recognizing hunger and fullness signs; Introducing solid food; Creating a home/childcare connection). Acceptability questions were embedded at the end of each module. Participants finished an evaluation survey and interview following completion. Results: The majority of participants were Black or African American (51.9%), non-Hispanic or Latino (96.3%), 31–50 years of age (59.2%), employed in a child care center (74.1%), and had > 10 years' experience caring for infants or toddlers (70.4%). At enrollment, most accurately defined RF as identifying hunger and fullness signals (90%), but fewer considered RF as providing developmentally appropriate foods (72%) or establishing routines and setting limits (59%). Preliminary results from 19 participants revealed that over 40% took 90–120 minutes to complete the program and 32% took 120–150 minutes to complete. Modules were viewed from a computer or laptop (90%), when at work (42%), in > 1 session (63%). Over 2/3 reported that the information was unique from other training materials. All participants reported that the videos were easy to view and the program was easy to navigate. The program included printed resources, but 25% of participants did not print these resources. Except for a few technical issues in responding to embedded questions, participants overwhelming expressed approval of the training module. Conclusions: This study addressed the critical first step of obtaining end-user acceptability of an online RF training for early childcare education providers. Necessary modifications will be made prior to evaluating efficacy and scale-up dissemination. Funding Sources: Nemours National Office of Policy and Prevention. National Academy of Sciences Nestlé Nutrition Institute